Statutory, effective, and optimal net tax schedules in Lithuania - Nerijus Cerniauskas; Alain Jousten (IZA Journal of Labor Policy, 2021)
We estimate effective and optimal net income tax schedules and compare them to the estimated statutory rates for the case of Lithuania for the period 2014-2015. Values of effective net tax rates are estimated from the survey of EU Statistics on Income and Living Conditions; the statutory net tax rates are estimated with the European tax-benefit simulator EUROMOD, whereas optimal net taxes are calculated via Saez (2002) methodology. We find that the three net tax schedules are similar for employees in the middle of the income distribution. At the bottom of the income distribution, optimal net tax schedules suggest higher in-work benefits. The net tax schedules diverge substantially for the self-employed. At the top of the income distribution, where the majority of self-employed are concentrated, the self-employed are required to pay 15 cents less net taxes per Euro than employees - and they effectively pay 29 cents less.
Keywords: H2; H21; 330; Optimal tax schedule; effective tax schedule; statutory tax schedule; taxes; transfers; employees; self-employed; Lithuania; Besteuerungsverfahren; Optimale Besteuerung; Einkommensteuer; Einkommensverteilung; Selbstständige; Angestellte; Litauen